2007
DOI: 10.1007/s10551-007-9605-z
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Paternalistic Leadership and Organizational Commitment: Investigating the Role of Climate Regarding Ethics

Abstract: ABSTRACT. One of the important factors influencing perceptions of the existence of an ethical climate is leader behaviors. It is argued that paternalistic leadership behaviors are developed to humanize and remoralize the workplace. In various studies, leadership behaviors and climate regarding ethics were evaluated as antecedents of organizational commitment. In this sense, the purpose of this study is to investigate the relationship between paternalistic leadership behaviors, climate regarding ethics and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
157
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(177 citation statements)
references
References 24 publications
11
157
1
8
Order By: Relevance
“…Likewise, Emery and Barker (2007) enlightened that transformational leadership style has the capability to enhance the employee commitment level. Equally, Erben and Guneser (2008) the result revealed that employee commitment level has increased by implementing transformational leadership style.…”
Section: Transformational Leadership Stylementioning
confidence: 91%
“…Likewise, Emery and Barker (2007) enlightened that transformational leadership style has the capability to enhance the employee commitment level. Equally, Erben and Guneser (2008) the result revealed that employee commitment level has increased by implementing transformational leadership style.…”
Section: Transformational Leadership Stylementioning
confidence: 91%
“…Employees who work under high moral leader tend to be more sociable and more active in organizational citizenship behavior [28]. Erben & Güneser (2007) demonstrates that the leader, who is the model for the employees and shows the ethically acceptable behavior, plays an important role in forming a psychologically meaningful perception of the organization's ethical processes and policies, and implies that it has an influence on the value commitment of employees [29]. Chou, Cheng, and Jen (2005), based on social exchange theory, found that employees with a high level of dependence on the organization are more likely to devote their jobs to achieving their goals, or to receive leadership attention and fair treatment [30].…”
Section: Derivation Of Theoretical Background and Hypothesismentioning
confidence: 99%
“…Using the same approach of Erben & Güne er (2008) and Dickson et al (2001), the term `climate regarding ethics` will be used in this study instead of the term `ethical climate`. As justified by Erben & Güne er (2008), this is because of two main reasons.…”
Section: Ethics In Organizations: Climate Culture and Code Of Ethicsmentioning
confidence: 99%
“…As justified by Erben & Güne er (2008), this is because of two main reasons. First, ethical climate implies that the behaviors are seen as ethical in the large society.…”
Section: Ethics In Organizations: Climate Culture and Code Of Ethicsmentioning
confidence: 99%
See 1 more Smart Citation